2005
DOI: 10.4103/0019-5545.43065
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of fluoxetine in the treatment of skin-picking

Abstract: The case of an 18-year-old girl with skin-picking is reported. The patient used to pick at healthy skin and small skin lesions, leading to ulceration, hyperpigmentation and disfigurement. She recovered almost fully with fluoxetine. The implications of diagnosis and the need for early treatment are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…This case report highlights the effectiveness of fluoxetine in the treatment of skin-picking and the need for early institution of treatment, which would not only curtail the period of suffering but ensure long-lasting improvement in such cases. [ 34 ]…”
Section: Case Reportsmentioning
confidence: 99%
“…This case report highlights the effectiveness of fluoxetine in the treatment of skin-picking and the need for early institution of treatment, which would not only curtail the period of suffering but ensure long-lasting improvement in such cases. [ 34 ]…”
Section: Case Reportsmentioning
confidence: 99%
“…Besides the above studies, case series and case reports have also shown usefulness of antidepressants in the management of trichotillomania with trichobezoar,[ 72 ] Atypical bulimia Nervosa,[ 73 ] Skin Picking,[ 74 ] Persistent developmental stuttering,[ 75 ] primary hypersomnia,[ 76 ] cognitive functioning in depression,[ 77 ] proctalgia fugax with dysthymia,[ 78 ] palmar-plantar hyperhidrosis,[ 79 ] severe resistant depression[ 80 ] etc. One open label study also evaluated the usefulness of sertraline in chronic tension type headache and showed that sertraline leads to significant reduction in mean analgesic intake per week, but there is no difference in reduction of headache index and frequency of headache.…”
Section: Introductionmentioning
confidence: 99%
“…1 Besides being a potential source of natural products for the treatment of asthma, coughs, rheumatism, cold, dysentery, fever 2,3 and other health problems, such as lowering of blood pressure, acceleration of deep respiration, inhibition of uterine motility, 4 extracts from L. camara are known to exert antioviposition, antifeedant, phagostimulant, repellence and adult emergence reduction effects on insect pests. 5,6 However, although the chemical composition of the essential oils from the plant material of L. camara from many countries is well documented, [7][8][9][10][11] …”
Section: Introductionmentioning
confidence: 99%